Issues to ponder on as we navigate the translation of academic texts from English into isiZulu - Mpanza, Choice D.; Dladla, Celimpilo P. (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
The purpose of this paper is to report on the experiences learnt from a translation project which involved the translation of academic study material from English into IsiZulu. The study material was commissioned for translation as part of a multilingual project being undertaken by one of the Higher Education Institutions (HEIs) in South Africa and came from different disciplines of study. The translator who had been assigned the project assembled a team of three qualified and experienced translators to collaborate on the project. Each translator was assigned to translate materials from the same discipline to avoid inconsistencies that could arise if different translators were assigned to handle texts from the same discipline. Computer Assisted Translation (CAT) tools were used during the translation process and different English-IsiZulu/IsiZulu-English lexicographic resources and various dictionaries were used as references when needed. Feedback received from the translators indicated that translating academic texts from English into isiZulu is quite challenging due to lack of equivalent terminology in isiZulu for most of the concepts used in academic English. However, it was found that it was possible to circumvent equivalence related challenges by using various translation strategies that are recommended by renowned translation scholars. Using qualitative data sourced from the translated texts and analysed using the theory of equivalence, this paper is a synopsis of the different translators’ experiences (challenges, hurdles and how they were resolved) and makes suggestions of what needs to be done to improve the translation of academic texts into indigenous African languages in the future.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 3, Volume 8, 2024 Special Issue
Keywords: Academic texts; Indigenous African languages; Multilingualism; Translation; Translation strategies; Multilingualism; English language -- Translating into Zulu; Academic writing; Translating and interpreting